A Goddess for the Greeks: Demeter as Identity Factor in Herodotus - Rodrigues, Nuno Simões (2020)
Within the Persian Wars narrative, Herodotus makes allusions to Demeter. One reference is presented in the context of the Persian occupation of Attica. In other passages, Herodotus writes that the battle of Plataia was near the sanctuary of Demeter, just as was the battle of Mykale. The Historian considers this was just a coincidence. But he also says that among the Greek forces were soldiers from Athens, Sparta, Corinth, and Megara. Therefore, Demeter emerges as a protective goddess of the Greeks and Herodotus represents the Goddess of Eleusis as well as the cults associated with her as panhellenic identity factors.